Joint Sequential Use of the Reassigned Smoothed Pseudo Wigner (Global Journals of Research in Engineering, 2023)
Digital intercept receivers are moving away from Fourier-based analysis towards classical time-frequency analysis techniques along with other novel analysis techniques for the purpose of analyzing low probability of intercept radar signals This paper presents a novel approach of the joint sequential use of the Reassigned Smooth Pseudo Wigner-Ville Distribution and the Hough Transform versus the Reassigned Smooth Pseudo Wigner-Ville Distribution for characterizing low probability of intercept triangular modulated frequency modulated continuous wave radar signals The metrics used for evaluation were - percent error of the chirp rate percent detection and lowest signal-to-noise ratio for signal detection Experimental results demonstrate that overall the joint sequential use of the Reassigned Smooth Pseudo Wigner-Ville Distribution and the Hough Transform signal processing techniques produced more accurate metrics than the Reassigned Smooth Pseudo Wigner-Ville Distribution signal processing technique An improvement in the accuracy of metrics may well equate to an increase in personnel safety